Assembly process of photovoltaic solar panels through TRIZ methodology - Cujaban , Sonia Roció
Solar photovoltaic panels are increasingly being used to generate electricity, and their characteristics can change over time depending on factors such as pollution, climate, and the aggressiveness of the environment in which they are installed. The scope of the study is limited to a glass laminating oven, in which vacuum and temperature are evaluated, which adapts the principle of the vacuum bag. This can join glass with EVA (ethyl vinyl acetate) film by melting it through vacuum and temperature on the glass to make laminated glass. The process is carried out step by step, describing the lamination process and the functionality of the panels, through the TRIZ methodology, which implements new technologies, materials, or processes that allow the identification of times and costs.